Vaginal cuff dehiscence resulting in small-bowel evisceration. A case report - Percalli, Luigi; Pricolo, Renato; Passalia, Luigi; Croce, Paolo; Ricco', Matteo; Berretta, Roberto; Marchesi, Federico (Acta Biomedica Atenei Parmensis, 2016)
Vaginal cuff dehiscence is a rare complication of hysterectomies which seems to be more frequent after surgery with laparoscopic suture of the cuff. We present a clinical case of evisceration of the small bowel emerging from vaginal cuff dehiscence, successfully repaired by positioning a low profile polypropylene ePTFE mesh*.